Legal Consequences of Using Other People's Identity in Online Loans - I Wayan Putu Sucana Aryana (Sociological Jurisprudence Journal, 2022)
Online loans that are part of Financial Technology create a new mode of crime, in which perpetrators can use other people's personal data to find the online loans. This action causes losses to the online loan service providers and people whose personal identities are used by the perpetrators to make online loans. For this reason, the problems discussed in this paper are: 1) How is the formulation of fintech based on online loans? 2) How is the protection of personal data in online loans? 3) What are the criminal sanctions for using other people's identities in online loans? To answer these problems, a normative juridical research method is used by using the literature sources as the primary source of legal material. Based on research originating from literature sources, criminal sanctions that can be imposed on perpetrators can be charged with Article 27 paragraph (1), (2), (3) or paragraph (4) of the Law on Information and Electronic Transactions, with a criminal penalty regulated in Article 45 of the Law on Information and Electronic Transactions with a maximum imprisonment of 4 (four) years and/or a maximum fine of Rp. 750,000,000 (seven hundred and fifty million rupiah). Judging from the elements in the criminal act of using false identities in making online loans, the criminal sanctions for using false identities on online loans can be suspected by Article 263 paragraph (1) of the Criminal Code regarding the crime of identity fraud, Article 378 of the Criminal Code on fraud, Article 311 paragraph (1) KUHP on slander/defamation.